Black Lesbian Identities in South Africa: Confronting a History of Denial - Janine E. Carlse (African Journal of Gender and Religion (AJGR))
Much of the existing literature on South African black lesbian identities has focussed on the prejudice and victimisation that they endure as subjects of homophobia in the form of hate speech and hate crimes, most notably brutal murders and corrective rape. However, not much has been written about the creative ways that black lesbians are fighting against these injustices that are built upon the historical erasure and denial of their very existence in Africa. By outlining three ‘denials’ of African female same-sex intimacy namely: the imperial denial and subsequent apartheid policing of same-sex intimacy, the denial of female same-sex intimacy through proclaiming it as un-African, and the conceptual denial through the lens of Euro-American feminist lesbian discourse; this article aims to show how black lesbians in South Africa are finding ways to confront these denials. In particular, some aspects of lives and work of self-identified lesbian activist photographer Zanele Muholi and lesbian sangoma Nkunzi Zandile Nkabinde will be analysed. Muholi and Nkabinde work hard to locate themselves within the public sphere, and engage in projects that aim to educate and build black lesbian communities, in an effort to encourage open dialogue of what it means to be an African lesbian. It can be argued that the voices of South African black lesbians are not only becoming more audible but also more nuanced, where imported notions of sexual identity are being questioned and adapted to their lived realities. Ultimately, this article aims to show how Muholi and Nkabinde provide examples of how reimaginings and negotiations of lesbian identities in (South) Africa are at once complex and essential, and this echoes Msibi’s (2014) call for “greater voices from Africa in theorising sexuality – a terrain long ignored in African scholarship.”